Organizational Readiness of the Ministry of Hajj and Umrah in Reforming the Governance of Hajj Pilgrimage Management in Indonesia - Suci Annisa; Laode Rudita (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
The establishment of the Ministry of Hajj and Umrah represents a significant step in the governance reform of the Hajj pilgrimage administration in Indonesia, aimed at improving the quality of public service delivery. However, such institutional transformation requires adequate organizational readiness to ensure that the reform is not limited to structural adjustments alone. This study aims to analyze the organizational readiness of the newly established Ministry of Hajj and Umrah in managing Hajj services. A descriptive qualitative approach was employed, with data collected through in-depth interviews, non-participant observation, and document analysis. Data analysis was conducted using the organizational readiness for change framework, which emphasizes the dimensions of change commitment and change efficacy. The findings indicate that organizational readiness remains in a transitional phase, characterized by relatively established structural readiness, but not yet fully supported by psychological and operational readiness. Commitment to change appears strong at the policy level but has not been fully internalized at the operational level. Meanwhile, confidence in the organization’s capacity to implement change continues to be shaped by limited institutional capacity and ongoing dependence on previous work patterns. This study highlights that organizational readiness within the context of a newly formed ministry should be understood as a dynamic process. The findings contribute theoretically to the development of the concept of organizational readiness and offer practical implications for strengthening governance reform in the administration of Hajj services in Indonesia.